EDUKASI PENEGAKAN KEDISIPLINAN KERJA PEGAWAI APARATUR SIPIL NEGARA MELALUI MEDIA POSTER PADA INSTANSI BADAN PENGEMBANGAN SUMBER DAYA MANUSIA PROVINSI SULAWESI SELATAN - Muh. Nur Hidayat Nurdin; Habiburrahman, Laode Muhammad Rezki, Feri Andriadi, Putri Ihlasul Ummah (JOURNAL OF COMMUNITY DEDICATION, 2022)
An organization needs humans as the main supporting resource to achieve the goals that have been set. Quality human resources will contribute to advancing the organization as a means of increasing work productivity. Employee performance is influenced by various factors, including: work environment, work discipline, organizational culture, leadership, and work motivation. In fact, there are still many civil servants who are still not optimal in carrying out their duties, especially in terms of work discipline. One of the preventive efforts in tackling this problem is by conducting education through print media such as posters regarding the rules of employee discipline and efforts to improve employee discipline. The purpose of this psychoeducational activity is to help grow the level of employee discipline, especially employees who work at the Human Resources Development Agency for South Sulawesi Province. The method used in the process of implementing this activity is by using the survey method, and psychoeducation in the form of posters. The targets for this activity are employees or ASN working at BPSDM South Sulawesi Province. This activity involves all employees or ASN working at BPSDM South Sulawesi Province, in order to provide benefits and the information provided. The result of this activity is that there is a positive response given from employees with a fairly good discussion in the framework of implementing related information about disciplinary regulations.